2023
DOI: 10.18280/ijsdp.181105
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Public Trust in Government in Somalia: An Empirical Analysis

Mohamed Yusuf Ahmed,
Abdi A. Gele,
Hassan Abdikadir Hussein
et al.

Abstract: Whether in a democratic or non-democratic system, public trust is a fundamental component for the survival and development of any political system. Using a comprehensive representative survey, this study examines and assesses the factors influencing public trust in the Somali government. Data were collected using a structured questionnaire completed by 354 Somali residents in Mogadishu. The data were examined using a quantitative structural equation modeling approach with SmartPLS 4. Additionally, our analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 88 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…addtitionally, they supported the notiona that transparency and open government initiatives have significantly enhanced legitimacy and trust in the government. Ahmed (2023) investigated the factors that contribute to public trust in the Somali government, and found that public trust in government is positively influenced by the quality of public services, participation in government, and transparency.…”
Section: Kulmie Mohamud and Ibrahimmentioning
confidence: 99%
“…addtitionally, they supported the notiona that transparency and open government initiatives have significantly enhanced legitimacy and trust in the government. Ahmed (2023) investigated the factors that contribute to public trust in the Somali government, and found that public trust in government is positively influenced by the quality of public services, participation in government, and transparency.…”
Section: Kulmie Mohamud and Ibrahimmentioning
confidence: 99%